Post merger profitability analysis of shareholders, evidence from Europe - Varun, Daga (2007)
The effects of takeovers on the value of both, target and bidder firms have been studied by many researchers. While in the United States there is extensive empirical evidence on the effects of consolidation on share price movements, the empirical literature remains limited in Europe. Reviewing the relevant literature suggests that the majority of previous work concludes that the bulk of mergers perform strongly pre merger and poorly afterwards. It is subject of the Hubris Hypothesis that bidders outperform the market pre merger and that bidder and target combined value is around zero. Systematically nonzero abnormal share returns after a particular event is inconsistent with market efficiency. The hubris hypothesis argues that bidders make systematic mistakes. Modigliani and Miller stress in their irrelevancy preposition that the means by which an investment is financed is irrelevant. Splitting merger deals into relevant characteristics suggests that the majority of research does not support this hypothesis. In terms of methodology, this study uses an event-study type approach, in which changes in the prices of specific financial market assets around the time of the announcement of the acquisition are analyzed. Different valuation approaches brought up in research and practical approaches are presented. The data is a sample of major European deals from 1995 to 2004. Abnormal returns are derived from the market model. The author finds that pre merger, companies outperform the benchmark and that during the event period there is insignificant underperformance. However, during the post event period, the sample firms significantly underperform on average. By and large, the main conclusion is that acquisitions destroy aggregate wealth. It is found that pre acquisition performance is not an indicator for post acquisition performance. Several effects are identified (higher combined bidder-target stock returns for friendly offers and lower for related offers). The long-run post-acquisition performance is insignificant for equity to shares offers.